1983
DOI: 10.4319/lo.1983.28.1.0133
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and nutrient interactions in controlling the activity and composition of the epilithic algal community of an arctic lake1

Abstract: The effects of grazing by the snail Lymnaea and enrichment with N and P were examined in the epilithic algal community of an arctic lake. Increased nutrients raised chlorophyll CL levels and primary production and favored the growth of filamentous green algae and coccoid blue-greens.Intensive grazing reduced algal concentration and activity. Grazing increased the relative abundance of small green and blue-green coccoid cells at the expense of larger (>20 pm) diatoms.Photosynthetic activity of snail feces was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 14 publications
6
60
1
Order By: Relevance
“…Cuker (1983) found that L. elodes egest viable cells that photosynthesize at 80% the rate of ungrazed substrates and hypothesized that these viable cells may take up inorganic N within the gut. This process would lead to the low concentrations of inorganic N observed in excretion and could result in a lowered N demand and a reduced need to fix N 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Cuker (1983) found that L. elodes egest viable cells that photosynthesize at 80% the rate of ungrazed substrates and hypothesized that these viable cells may take up inorganic N within the gut. This process would lead to the low concentrations of inorganic N observed in excretion and could result in a lowered N demand and a reduced need to fix N 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Periphyton grazed by snails is characterized by reduced three-dimensional structure brought about by the disproportionate mortality of overstory algae (Sumner and McIntire 1982;Hunter and Russell-Hunter 1983). Small, adnate algal cells that are not cropped by the snails often dominate these snail-grazed communities (Patrick 1970;Cuker 1983;Hunter and Russell-Hunter 1983 Creek, resulting in a ratio of ambient biomasses that approximated 2 to 1 (Neophylax to Ameletus). The 2 : 1 ratio implies that the absolute value of Ameletus regression coefficients had to be twice those of Neophylax for Ameletus to have had an equivalent ambient effect.…”
Section: Resultsmentioning
confidence: 99%
“…Miura and Wang (1985) observed a doubling of the photosynthetic activity of cyanobacteria excreted by bighead (Aristichthys nobilis). From investigations of snails fed cyanobacteria, it had been supposed that undigested cyanobacterial cells can take up nutrients from the alimentary canal during passage (Cuker 1983). Phosphorus uptake was demonstrated by microautoradiography for the green algae Sphaerocystis after passage through Daphnia (Porter 1976) and by uptake of radiolabeled P for the green algae Scenedesmus in Daphnia (Boersma pers.…”
Section: Phosphorus Uptake By Microcystis During Passage Through Fishmentioning
confidence: 99%